Comparison of four risk assessment scales in predicting the risk of intraoperative acquired pressure injury in adult surgical patients: a prospective study - Yuan Chen; Wei Wang; QianJian Qian; BeiWen Wu (Journal of International Medical Research, 2023)
Objective To develop and compare four predictive models for intraoperative acquired pressure injury (IAPI) in surgical patients. Methods One hundred patients undergoing various surgeries (hepatobiliary, pancreas, spleen, gastrointestinal, and cardiac surgeries) at Ruijin Hospital from November 2021 to September 2022 were included in this prospective cohort study. Four pressure injury risk assessment scales were used to measure the pressure injury risk: the Braden scale, Munro Pressure Injury Risk Assessment Scale, Scott Triggers tool, and CORN Intraoperative Acquired Pressure Injury Risk Assessment Scale. The patients were divided into the IAPI group and non-IAPI group. Results In total, 37% of patients (37/100) developed class I/stage pressure injury (erythema) after surgery, which resolved within 2 hours after surgery in 86.49% of cases and further progressed to class II/stage or higher pressure injury within 6 days in 15.63% of cases. The application effects of the four commonly used risk assessment tools were compared with the sensitivity, specificity, and area under the receiver operating characteristic curve. The Munro Scale showed the best sensitivity and area under the receiver operating characteristic curve among the four tools for postoperative assessment, but its specificity was only 20.63. Conclusions More appropriate assessment tools are required for IAPI risk evaluation.